Synthesis and Characterization of Activated Carbon/Alginate/Nanocellulose-Cu Composites - Syahirah, Atikah Nur; Jasmidi, Jasmidi; Muchtar, Zainuddin; Rahmah, Siti; Pulungan, Ahmad Shafwan; Zubir, Moondra; Selly, Rini; Faradilla, Putri (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
OPEFB is one source of natural fiber-based composites which have the potential to become activated carbon and nanocellulose. This study aims to synthesize and characterize the activated carbon/alginate/nanocellulose-Cu composite. The characterization used in this study is FTIR and PSA. The synthesis of activated carbon/alginate/nanocellulose-Cu composites began with a process of carbonization and activation with H3PO4 to produce Activated Carbon. Followed by a bleaching process with NaClO2 and a delignification process with Na2SO3 and NaOH to produce Nanocellulose. Alginate using commercial alginate. Furthermore, the three ingredients were mixed until homogeneous and put into a 0.1M CuSO4 solution to produce beads. The results of the characterization of characterization of PSA Nanocellulose obtained a particle size of 41.05 nm and the result of FTIR characterization on the activated carbon/alginate/nanocellulose-Cu composite contained the functional group OH group, triple C bond from stretching alkyne, C=C aromatic group, C-H alkane group, C-O group, the P=O stretching vibration of the P-O-C group and the alcohol OH group expressing the active carbon; there are functional groups of hydroxyl (OH), carboxyl, carbonyl, and C-O-C and “COOH bonds which represent alginate and there are OH functional groups, stretching C-H bonds, C-O stretching, stretching C-C, and Î²- glucosidic bonds between glucose units which indicate nanocellulose.